Paving the Way for Women’s Economic Inclusion in the Gulf Cooperation Council - World Bank Group (World Bank, Washington, DC, 2016)
This engagement note in the Gulf Cooperation Council (GCC) aims to identify entry points that respond to the strategic goals and country development priorities announced by GCC member states. This note provides an overview of the recent progress and key economic challenges facing women in GCC countries of the Middle East and North Africa (MENA) region. The note builds on GCC country priorities and aims to support ongoing governmental efforts toward economic diversification and fostering knowledge-based economies. All six countries have developed national development plans that stress the importance of moving away from the heavy reliance on hydrocarbons and toward investing in human capital through quality education and strategic training in productive sectors such as science and technology.